The plant growth-promoting Burkholderia vietnamiensis produces acyl-homoserine lactones and modulates the quorum-sensing signaling in the rhizosphere - Poonguzhali, Selvaraj; Kim, Kiyoon; Madhaiyan, Munusamy; Sa, Tongmin (Frontiers in Microbiology, 2025)
The genus Burkholderia, comprising over 60 species, represents a highly diverse group of bacteria known for their exceptional metabolic versatility. Quorum sensing (QS), a mechanism of cell-density-dependent gene regulation, plays a critical role in host colonization, environmental adaptation, and, in many cases, pathogenesis. Due to the established link between QS and virulence, most QS studies in Burkholderia cepacia complex (Bcc) species have focused on pathogenic strains. In contrast, comparatively little attention has been given to QS in plant growth-promoting (PGP) Burkholderia strains. In this study, we investigated the QS systems of Burkholderia vietnamiensis strains with plant growth-promoting potential. We identified two functional QS circuits, CepI/R and BviI/R, responsible for the synthesis of distinct AHL molecules with N-decanoyl homoserine lactone (C10-HSL) as the dominant molecule. In B. vietnamiensis CBMB40, both synthases contributed to the production of N-hexanoyl (C6-) and N-Octanoyl (C8-) homoserine lactones, while bviI synthase contributed to the production of C10-HSL and N-Dodecanoyl (C12-) homoserine lactones. The AHLs produced by CBMB40 could be detected in plant tissues, and they served as interpopulation signaling molecules within the rhizosphere. A random transposon mutagenesis approach was employed to generate an AHL-deficient mutant (ΔCBMB40). The mutant exhibited an extended log phase, reduced protease activity, and loss of antagonism against Erwinia carotovora subsp. carotovora, as well as diminished activity against multiple fungal pathogens. Notably, the addition of AHL extracts from the wild-type strain restored antagonistic activity in the mutant. Furthermore, in vitro potato tuber assays and pot culture experiments in red pepper confirmed that AHL-mediated QS is essential for the biocontrol potential of CBMB40. Together, these findings enhance our understanding of QS-regulated functions in PGP B. vietnamiensis CBMB40 and support its potential application as a sustainable biocontrol agent in agriculture. Importantly, this study underscores the potential of using PGP bacteria (PGPB) to prime plant defenses, offering a biologically meaningful and ecologically sustainable alternative to genetically modified plants engineered with AHL synthase genes. AHL-mediated cross-communication in the rhizosphere may further disrupt pathogenic signaling, opening new avenues for microbiome-based crop protection strategies.